The Nexus Between Digital Governance and Rural Community Participation: A Scopus-Based Bibliometric Review - Adam Gamgulu; Rahmat Abd Fatah (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
This study examines the nexus between digital governance and rural community participation through a bibliometric approach based on Scopus-indexed publications from 2011 to 2026. The rapid advancement of digital technologies has transformed public governance systems, particularly in rural contexts where access, inclusion, and participation remain critical challenges. Using the PRISMA framework, 512 documents were initially identified and systematically filtered to obtain 30 highly relevant articles. The data were analyzed using VOSviewer to map the structure, trends, and evolution of research in this field. The findings reveal a significant increase in scholarly attention over the past decade, indicating a growing global interest in integrating digital governance with rural development. Network visualization identifies four major thematic clusters: (1) digital governance and rural development, (2) good governance and citizen participation, (3) technology and public service delivery, and (4) academic and methodological dimensions. Density and overlay analyses further demonstrate a shift from traditional e-government approaches toward more complex and integrated concepts such as smart governance, digital inclusion, and rural digitalization. The study highlights that digital governance is shaped by three interrelated dimensions: technological innovation, governance quality, and community participation. However, persistent challenges such as the digital divide, limited infrastructure, and low digital literacy hinder its effective implementation in rural areas. This research contributes to the literature by providing a comprehensive bibliometric mapping and theoretical synthesis of digital governance in rural contexts. It also offers policy insights for developing inclusive, participatory, and sustainable digital governance frameworks at the global level.